The Kynurenine 3-Monooxygenase Encoding Gene, BcKMO, Is Involved in the Growth, Development, and Pathogenicity of Botrytis cinerea - Zhang, Kang; Yuan, Xuemei; Zang, Jinping; Wang, Min; Zhao, Fuxin; Li, Peifen; Cao, Hongzhe; Han, Jianmin; Xing, Jihong; Dong, Jingao (Frontiers in Microbiology, 2018)
A pathogenic mutant, BCG183, was obtained by screening the T-DNA insertion library of Botrytis cinerea. A novel pathogenicity-related gene BcKMO, which encodes kynurenine 3-monooxygenase (KMO), was isolated and identified via thermal asymmetric interlaced PCR, bioinformatics analyses, and KMO activity measurement. The mutant BCG183 grew slowly, did not produce conidia and sclerotia, had slender hyphae, and presented enhanced pathogenicity. The phenotype and pathogenicity of the BcKMO-complementing mutant (BCG183/BcKMO) were similar to those of the wild-type (WT) strain. The activities of polymethylgalacturonase, polygalacturonase, and toxins were significantly higher, whereas acid production was significantly decreased in the mutant BCG183, when compared with those in the WT and BCG183/BcKMO. Moreover, the sensitivity of mutant BCG183 to NaCl and KCl was remarkably increased, whereas that to fluconazole, Congo Red, menadione, H2O2, and SQ22536 and U0126 (cAMP-dependent protein kinase (cAMP) and mitogen-activated protein kinase (MAPK) signaling pathways inhibitors, respectively) were significantly decreased compared with the other strains. Furthermore, the key genes involved in the cAMP and MAPK signaling pathways, Pka1, Pka2, PkaR, Bcg2, Bcg3, bmp1, and bmp3, were significantly upregulated or downregulated in the mutant BCG183. BcKMO expression levels were also upregulated or downregulated in the RNAi mutants of the key genes involved in the cAMP and MAPK signaling pathways. These findings indicated that BcKMO positively regulates growth and development, but negatively regulates pathogenicity of B. cinerea. Furthermore, BcKMO was found to be involved in controlling cell wall degrading enzymes activity, toxins activity, acid production, and cell wall integrity, and participate in cAMP and MAPK signaling pathways of B. cinerea.